Fennera holthuisi sp. nov., a new coral-associated pontoniine shrimp (Decapoda: Palaemonidae: Pontoniinae) from Moorea, French Polynesia - Marin, Ivan (Zootaxa, 2011)
The second species of the genus Fennera Holthuis, 1951, F. holthuisi sp. nov., is described, based on a female specimen collected at Moorea, French Polynesia. The new species clearly differs from F. chacei Holthuis, 1951 by carinated dactylus of major pereiopod II (vs. flattened in F. chacei), more robust segments and feebly developed fingers of minor pereiopod II, and proportions of the distal segments of ambulatory pereiopod III. The holotype female of F. chacei Holthuis, 1951 and specimens from the type series are re-examined and re-described, based on specimens from the Pacific coast of Panama and Columbia.